Characterization of two new HLA‐B alleles, HLA‐B*07:299 and HLA‐B*35:350. (31st January 2018) - Balas, A.; Alenda, R.; López‐Hernández, R.; Sánchez‐García, F.; Vicario, J. L.
Abstract : Two novel HLA‐B alleles, B*07:299 and B*35:350, were characterized by genomic full‐length sequencing.